2002
DOI: 10.1063/1.1513463
|View full text |Cite
|
Sign up to set email alerts
|

Host–guest charge transfer states: CN doped Kr and Xe

Abstract: Articles you may be interested inDipole oscillator strength distributions with improved high-energy behavior: Dipole sum rules and dispersion coefficients for Ne, Ar, Kr, and Xe revisited

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Experimentally, we have recorded the UV absorption of acetylene photofragments in Ar, Kr, and Xe matrixes. For the Kr matrix, a previously unreported set of bands in the 188−209 nm region was found to belong to the same absorber, and by comparison of the spectrum to that of Cl and CN doped Kr matrixes and by theoretical predictions, the band set has been assigned to the C 2 Kr n neutral to C 2 - Kr n + charge-transfer transitions. , …”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Experimentally, we have recorded the UV absorption of acetylene photofragments in Ar, Kr, and Xe matrixes. For the Kr matrix, a previously unreported set of bands in the 188−209 nm region was found to belong to the same absorber, and by comparison of the spectrum to that of Cl and CN doped Kr matrixes and by theoretical predictions, the band set has been assigned to the C 2 Kr n neutral to C 2 - Kr n + charge-transfer transitions. , …”
Section: Discussionmentioning
confidence: 84%
“…As the energy of the CT states is dictated by the ionization potential of the rare gas host, the absorption band origins should shift accordingly. This would predict origins for the CT bands as Ar (161 nm), Kr (209 nm), and Xe (306 nm) . For the case of Ar, the presence of the strong deuterium lamp background in the 155−165 nm region could mask the CT absorptions and they could not be seen (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a computational perspective, nonadiabatic dynamics simulations that include consideration of the presence of multiple electronic states are significantly more expensive than adiabatic dynamics where atomic trajectories follow a single adiabatic potential energy hypersurface. For molecules containing heavy atoms, it has been shown 13,14 that DIM can incorporate spin-orbit coupling. 1,2 Although many semiclassical approaches have been developed, 3 the Erhenfest or mean-field 4 and surface-hopping 5 approaches are often used 6-8 because of their relative simplicity and proven ability to quantitatively reproduce experimental spectra from photoexcitation and scattering measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Applying the preparation, interrogation, and manipulation procedures presented in this paper for a matrixisolated CN rotor would contribute to the research field of coherent control of rotational degrees of freedom in condensed phase systems. Several studies [20][21][22][23][24] have shown that CN radicals are relatively free rotors when trapped in solid Xe matrices, despite the pronounced, ∼1000 cm −1 red shift of the electronic B ← X transition band. The preserved high symmetry of the cavity renders an effectively isotropic interaction potential and decoupling between the impurity and its environment.…”
Section: Introductionmentioning
confidence: 99%